The influence of cultural and social capitals on immigrant entrepreneurship : a cross-cultural study - Raupp, Monique (2017)
This research proposes understanding the influences that cultural and social capitals exert on the immigrant entrepreneurship process of individuals who decided to move to a nation that is economically and culturally different from their home countries. Immigration is an increasingly phenomenon that affects several countries around the world, some of them having their economies heavily related to this group of people. When trying to find a job placement in the new market, most immigrants face difficulties such as language barriers, taste discrimination and lack of recognition of their accumulated capitals. A common option to reduce such challenges is pursuing entrepreneurship, which is usually related to fields that possess less influence of the aforementioned barriers, and that do not require much specific knowledge. Nevertheless, immigrant entrepreneurship has important differences when being compared to other types of entrepreneurship, and this fact is usually due to cultural and social aspects. In this context, it is inquired: “how does both the cultural and social capitals linked to the entrepreneur's country of origin relate to his/her opportunities to undertake and sustain an enterprise of the culinary field in a culturally and economically distinct country?”. In order to address this inquiry, four immigrant restaurant owners were interviewed. Two of them immigrated to England, coming from Latin American underdeveloped countries, while the other two immigrated to Brazil, coming from European developed nations. The semistructured interview script had 16 questions formulated according to Pierre Bourdieu’s concepts of cultural and social capitals, aiming at qualitatively understanding in what consisted these two types of capitals of each entrepreneur, as well as understanding how they related to each moment of their individual entrepreneurial journeys. The interviews were conducted in person in both cities of London and Florianópolis, during the first semester of 2016. The results show that all of the immigrant entrepreneurs faced some type of cultural shock and discrimination during their entrepreneurship processes, which is most evident in the Latin entrepreneurs. Regarding the influence of their cultural capitals, family influences, accumulated knowledge and professional experiences greatly influenced their entrepreneurship process, and the entrepreneurs who possessed the higher amount of accumulated and recognized cultural capital faced far less difficulties as immigrant entrepreneurs. When talking about their social capitals, the entrepreneurs mostly relied on their social connections with people born in their home countries or in nations more culturally similar to their own. These relations, however, were of different natures between the Latin and European immigrants. The social capital that mostly influenced the Latin entrepreneurs consisted on their families and Latin immigrant friends, who faced similar obstacles as they did. On the other hand, the social capital the European entrepreneurs relied during their entrepreneurial processes were friends born in their home countries, who are also renowned professionals in the culinary field and that were able to share valuable knowledge with them. This study contributes to the entrepreneurship field by addressing the emerging immigrant entrepreneurship topic, which is still being consolidated and has important gaps such as this one to be fulfilled.